Mongolia : Accounting and Auditing - World Bank (Washington, DC, 2012)
This report provides an assessment of corporate sector accounting, financial reporting, and auditing requirements and practices within the enterprise and financial sectors in Mongolia. For purposes of this report, the corporate sector includes all private sector and state-owned enterprises. The report uses International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA) as benchmarks and draws on international experience and good practices in the field of accounting and audit regulation to evaluate institutional capacity and make policy recommendations. Since 1993, the World Bank and other development partners of Mongolia have provided financial and technical support to help Mongolia develop a legal framework, facilitate accounting education and adoption of IFRS and ISA by enterprises, constitute a new professional body, establish the examination of certified public accountants, and strengthen accounting and auditing in both public and private sectors. As a result, Mongolia has made significant changes from the old accounting for planned economic system to a new market-oriented accounting system that follows international good practices. All key economic sectors in Mongolia rely on high-quality financial information, which requires high-quality private sector accounting and auditing. Reforms, liberalization, and deregulation to further enhance the Mongolian business environment must be supported by enhanced financial transparency and improved accounting and auditing practices. Increased levels of both foreign direct investment and domestic investment demand higher-quality financial information consistent with international standards. Continuing the strengthening and development of financial reporting, accounting and auditing, and the regulatory framework that governs them, will bring benefits to Mongolia and its citizens. In this context, this report sets out policy recommendations to enhance the quality of corporate financial reporting and foster a financial reporting platform conducive to sustainable private and financial sector growth, thus increasing access to global financial markets and other tools of the market economy.